Future Prospects for Pharmacogenomics of Immune Checkpoint Inhibitors Cardiotoxicity - Aryantha, Hasna Firdaus; Wisasani, Amiiratu Muthiia; Anggadiredja, Kusnandar; Zazuli, Zulfan (Indonesian Journal of Clinical Pharmacy, 2024)
Immune checkpoint inhibitors (ICIs), including PD-1, PD-L1, and CTLA-4 inhibitors, have revolutionized cancer therapy but are associated with immune-related adverse events (IRAEs). Among these, ICI-associated cardiotoxicity is an uncommon yet serious complication, often resistant to glucocorticoid therapy, which effectively manages most IRAEs. A pharmacogenomic approach might be useful in prescribing ICIs and screening for relevant clinically measurable phenotypes such as the history of autoimmune diseases and cardiovascular disorders. This review explores the impact of genetic variations on ICI-associated cardiotoxicity, the mechanistic basis behind it, potential clinical applications, and directions of the future on how pharmacogenomics can assist oncologists in reducing the risk of cardiotoxicity. Evidence-based hypotheses on how ICI-associated cardiotoxicity occurs suggest that genetic differences might play a role in ICI response, especially regarding cardiotoxic IRAEs. Pharmacogenomic studies and multi-omics profiling might provide valuable insight regarding ICI-induced cardiotoxicity. They could be implemented to make fine-tuned clinical decisions for individual patients in the future.